UMKM Sosialisasi Dan Pelatihan Pajak Untuk UMKM Binaan BKM Ikhlas Persatuan - Arief, Muhammad Arief; Fadhilah, Dea (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2024)
The activities of the community service program carried out are to help the regional office of DGT North Sumatra I to socialise Government Regulation No. 23 of 2018, which came into effect on 1 July 2018, to small and medium enterprises tax laws so that the data will help the state to increase the revenue of the tax sector. This service was carried out in Medan and its surroundings. The purpose of the issuance of this government regulation is as a learning period for taxpayers with a certain gross circulation to be able to organise their bookkeeping before being subject to income tax under the general regime so that it is easier to carry out their tax obligations.Entrepreneurs can understand the meaning of tax and the importance of tax for entrepreneurs PP no. 23 of 2018, which is intended for UMKM, and can make financial records, calculate the amount of tax to be paid and tax reporting, this can be seen from the suitability of the training materials with the needs of small and medium business actors to increase the understanding of taxation, then a positive response seen from the enthusiasm of the training participants to participate in service activities and most of the Eighty percent (80%) participants have understood about taxation, the importance of tax for small businesses and development with entrepreneurs understand the implementation of PP No. 23 of 2018 for MSMEs, can keep financial records, calculate the amount of tax to be paid and file tax returns. Year 2018 for UMKM, can make financial records, calculate the amount of tax that must be paid, as well as the amount of tax that must be paid.